2011
DOI: 10.3945/ajcn.110.008359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of a 2-y soy isoflavone supplementation in menopausal women

Abstract: Daily supplementation for 2 y with 80-120 mg soy hypocotyl isoflavones has minimal risk in healthy menopausal women. This trial was registered at clinicaltrials.gov as NCT00665860.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 53 publications
6
66
1
Order By: Relevance
“…42 mg/kg b.wt per day in a range from 30 to 55 mg/kg/ day. Such a dose is relatively high-a human equivalent dosage [25] can only be reached by dietary supplements using a dose, which is three to four times higher than the maximum dose commonly used for treatment of postmenopausal complaints [74][75][76][77][78].…”
Section: Genisteinmentioning
confidence: 99%
“…42 mg/kg b.wt per day in a range from 30 to 55 mg/kg/ day. Such a dose is relatively high-a human equivalent dosage [25] can only be reached by dietary supplements using a dose, which is three to four times higher than the maximum dose commonly used for treatment of postmenopausal complaints [74][75][76][77][78].…”
Section: Genisteinmentioning
confidence: 99%
“…Peri-and post-menopausal women with a family history of breast cancer are a sub-population in Western society that increasingly is considered vulnerable for unregulated and selfadministrated consumption of dietary soy supplements (BfR, 2007;Doerge et al, 2000;Maskarinec, 2013). Despite their beneficial effects for human health and large societal acceptance by consumers, potential adverse effects as suggested in in vitro and in vivo experiments, and in clinical trials, raise questions about the safety of high dosages of phytoestrogens (Andres et al, 2011;Haines et al, 2012;Rietjens et al, 2013;Steinberg et al, 2011). However, most of the in vitro estrogenicity experiments used biologically active aglycones, which generally make up <1-2% of the total isoflavone levels present in blood (Gu et al, 2006;Hosoda et al, 2010;Sesink et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although hormone replacement therapy (HRT) can help to prevent and treat the menopausal syndromes, the side effects of HRT, such an increased risk of developing breast and endometrial cancer, prevent the acceptance of HRT [4,5] . Recently, reliable evidence has indicated that phytoestrogens offer the www.chinaphar.com Ma HR et al Acta Pharmacologica Sinica npg best potential therapy for menopausal women because they are safe and have a high compliance rate [6,7] . Increasing numbers of women are using phytoestrogens as an alternative therapy for menopausal syndromes.…”
Section: Introductionmentioning
confidence: 99%